STRUKTUR DAN FUNGSI SOSIAL UNGKAPAN LARANGAN TENTANG TUBUH MANUSIA DAN OBAT-OBATAN DI DESA TALAGO GUNUNG KECAMATAN BARANGIN KOTA SAWAHLUNTO - Anggraeni, Indri; Hayati, Yenni; Nst., Muhammad Ismail (Jurnal Bahasa dan Sastra, 2018)
This study aims to describe the structure and social functions of the expression prohibition of the human body and drugs in the village of Talago Gunung Village Barangin District Sawahlunto. The theory used in this research is folklore theory. This research type is qualitative research with descriptive method. Data obtained from oral sources and words informants community of Talago Gunung Village Barangin Sub District Sawahlunto equipped with the recording phase, then transcribed into the form of writing. The transcribed results are translated, as well as the collection of data on the story environment conducted by recording, observation and interview techniques. Data is validated by triangulation technique,furthermore, the data were analyzed by data inventory, classification / data analysis, discussion, conclusion, and reporting. The result of this research is social structure and function of people's trust expression prohibition society of Talago Gunung Village Barangin Sub District Sawahlunto, can be concluded that there are 52 expression prohibition, that is 45 phrases which is structure of two parts and 7 phrase which is structure of three parts. Furthermore, there are 6 expressions which serve as a function of the reinforcement of religious emotion or belief, 2 as a function of the imaginary projection system, 36 educational functions, and 52 expressions of prohibiting and enjoining and entertaining functions are not found in the data.Keywords: structure, functions, expression, prohibition